Teknik Flebotomi (Fasdhu) Sebagai Upaya Pratama Untuk Menurunkan Tekanan Darah Pada Penderita Hipertensi - Darmadi; Eli Yusrita; Asiska Permata Dewi; Ismaningsih; Nural Hasbi (Journal of Empowerment Community, 2024)
Phlebotomy technique (Fasdhu) is a technique used to remove blood from the functioning cubital vein. This technique is useful for reducing excess levels in the body, one of which is high blood pressure (hypertension). Many methods have been used to reduce high blood pressure, including synthetic drugs, consuming herbal medicines and several other efforts that are thought to be able to reduce blood pressure. The aim of this service is to hope that hypertension sufferers will return to normal blood pressure after carrying out the phlebotomy (fasdhu) technique. The method or implementation stages used in this service begin with providing education about hypertension, followed by the next stage of measuring blood pressure, the next stage of removing blood using the phlebotomy technique (fasdhu) and the final stage of measuring blood pressure after treatment with the phlebotomy technique. From the treatment carried out on 10 respondents who experienced high blood pressure, the average blood pressure before the phlebotomy technique (fasdhu) treatment was 172/88.5 mmHg, while after the treatment the average blood pressure was 148.2/88.3 mmHg. From the results of the phlebotomy technique (fasdhu) treatment that has been carried out, the fasdhu technique treatment is able to reduce high blood pressure. Key words: Phlebotomy, fasdhu, hypertension.